Development of A Solar-Powered Weighbridge System Using Load Cells in Quarry Site - Mohd Zamri, Nur Syahirah; Mohamad, Khairul Anuar; Alias, Afishah; Razali, El-Farabi; Nordin, Mohammad Syahmi (Evolution in Electrical and Electronic Engineering, 2022)
Weighbridge gives high accuracy and efficiency in measuring the weights of loads to ensure safety and compliance with road transport legislation. However, at a remote quarry site, the installation of a weighbridge had been an issue as the electricity supply is one of the problems that need to be faced since the operation of the weighing truck may fail whenever an electrical disruption occurs. In addition, the weighbridge that is widely used in industries for weighing vehicles is not flexible especially for temporary worksites as it cannot be moved from one site to another site. This project proposed the photovoltaic system to power the weighbridge system and develop the prototype to represent the element of a real portable weighbridge at the remote quarry site. The standalone photovoltaic system consists of a PV panel, rechargeable battery, PWM charge controller and weighing system which is controlled by Arduino Uno. The measurement results proved that the weighing scale with four load cells mounted separately indicates an accuracy of about 99 % since less difference error from the actual weight. Therefore, the development of portable weighbridges with four separate platforms each platform weighing each of the tire’s trucks and powered by the solar system is very suitable to be applied in a real application to obtain accurate measurement data.